Digital transformation in government institutions according to Vision 2030 - Saqqat, Ahmed Adel; Aziz Rahman, Ryan Adnan (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to know the availability of digital transformation requirements in government institutions in accordance with Vision 2030, and the study was applied to Al Noor Hospital in Makkah Al Mukarramah as a case study. The study relied on the descriptive analytical approach to reach scientific results that reveal the reality of the digital transformation in the hospital, and the questionnaire was used as an appropriate tool for this research. They analyzed it scientifically and interpreted its results. The study reached a number of results, the most important of which are:The senior management of Al Noor Hospital provides adequate support towards digital transformation and the right time towards digital transformation efforts in all hospital transactions. Al Noor Hospital also has the appropriate strategic directions for digital transformation to transform threats into opportunities to be benefited from in the future in the digital transformation process.The study reached a number of recommendations, the most important of which are: Enhancing the hospital’s senior management’s support for digital transformation by providing the hospital administration with a special budget to develop the quality of its electronic services as an entry point for digital transformation. And the hospital’s allocation of an effective incentive system for distinguished human resources, which encourages the rapid transformation of the application of management by electronic means.